Job Analysis in Human Resource Management at TPQ Istikmal Surabaya: A Synergy of Theory and Field Practice - Meli Handayani; Rafidah Arif; Mardiyah (Jawda: Journal of Islamic Education Management, 2026)
Job analysis is a fundamental instrument in human resource management (HRM) that supports role clarity, task distribution, and professional accountability in educational institutions; however, its application in nonformal Islamic education institutions remains limited. This study aims to examine the implementation of job analysis in managing human resources at Taman Pendidikan Al-Qur’an (TPQ) Istikmal Surabaya by integrating theoretical perspectives with field practices grounded in Islamic educational values. Employing a qualitative descriptive approach, the study combines a literature review with field research. Data were collected through purposive in-depth interviews with TPQ leaders and teachers, participatory observation of instructional and administrative activities, and document analysis, and were analyzed using descriptive qualitative analysis with triangulation to ensure credibility. The findings reveal that job analysis at TPQ Istikmal Surabaya has been substantively implemented through practical stages of role identification, task allocation, and competency-based placement, although formal documentation remains limited. This implementation contributes to reduced role overlap, improved coordination, and enhanced effectiveness of HRM while maintaining values of sincerity, responsibility, and consultation. The study concludes that job analysis functions as a strategic HRM instrument in nonformal Islamic education and recommends gradual formalization to strengthen professionalism and institutional sustainability.